2019
DOI: 10.1016/j.cels.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

tRNA Methylation Is a Global Determinant of Bacterial Multi-drug Resistance

Abstract: During production of this paper, an incompletely corrected manuscript was mistakenly approved for publication at the proof stage. As a result, the originally published version of this article contained many small errors in the list shown below. None of these errors affect the conclusions of the paper; they have been corrected online. Cell Press apologizes for the errors and any inconvenience that may have resulted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…These inferences were verified in several ways. The Nile Red assay for efflux 30,31 confirmed a higher rate of efflux, stimulated by AcrA (Fig. 3b).…”
Section: Dead Cells Release Acra As a Necrosignalmentioning
confidence: 59%
See 1 more Smart Citation
“…These inferences were verified in several ways. The Nile Red assay for efflux 30,31 confirmed a higher rate of efflux, stimulated by AcrA (Fig. 3b).…”
Section: Dead Cells Release Acra As a Necrosignalmentioning
confidence: 59%
“…3b). The Alamar Blue assay for membrane permeability 30,32 showed lower permeability, unaffected by AcrA (Fig. 3c).…”
Section: Dead Cells Release Acra As a Necrosignalmentioning
confidence: 93%
“…Thus, despite being placed at the same position, the chemical reactivity of acp 3 U47 to biotin-SA conjugation can differ depending on the tRNA sequence. Although both tRNA Arg/ICG and tRNA Lys/mnm5s2UUU were overexpressed in cells, the level of post-transcriptional modification to synthesize acp 3 U47 was likely stoichiometric under the expression condition, as evidenced by mass spectrometry quantification of other post-transcriptional modifications [ 40 ]. In contrast to the low reactivity of acp 3 U47, the reactivity of the alkyl-amine of the aminoacyl group after aminoacylation was robust.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that tRNA modi cation is required for cold adaptation in extreme-thermophilic bacteria [49]. In addition, it has been shown that tRNA modi cation during environmental stress is critical [50]. The gene trmD (encoding guanine-N(1)-methyltransferase) is required for multi-drug resistance in E. coli, since it provides a control mechanism to translation of membrane proteins [50].…”
Section: Translation Regulation Through Translation Initiation Factormentioning
confidence: 99%
“…In addition, it has been shown that tRNA modi cation during environmental stress is critical [50]. The gene trmD (encoding guanine-N(1)-methyltransferase) is required for multi-drug resistance in E. coli, since it provides a control mechanism to translation of membrane proteins [50]. It is possible that tRNA modi cation in the three lactic acid bacteria studied provides a similar control system for cold-shock response genes, promoting their translation.…”
Section: Translation Regulation Through Translation Initiation Factormentioning
confidence: 99%